Same‐day discharge after cryoballoon ablation of atrial fibrillation: A multicenter experience. (29th December 2020) - Kowalski, Marcin; Parikh, Valay; Salcido, Jose R.; Chalfoun, Nagib; Albano, Alfred; O'Neill, Padraig G.; Bowers, Mark R.; Gauri, Andre; Braegelmann, Kendra M.; Lim, Hae W.; Akhrass, Philippe; Shah, Rina; et al.
Abstract: Background: It is common practice to observe patients during an overnight stay (ONS) following a catheter ablation procedure for the treatment of atrial fibrillation (AF). Objectives: To investigate the safety and economic impact of a same‐day discharge (SDD) protocol after cryoballoon ablation for treatment of AF in high‐volume, geographically diverse US hospitals. Methods: We retrospectively reviewed 2374 consecutive patients (1119 SDD and 1180 ONS) who underwent cryoballoon ablation for AF at three US centers. Baseline characteristics, acute procedure‐related complications, and longer‐term evaluations of safety were recorded during routine clinical follow‐up. The mean cost of an ONS was used in a one‐way sensitivity analysis to evaluate yearly cost savings as a function of the percentage of SDD cases per year. Results: The SDD and ONS cohorts were predominately male (69% vs. 67%; p = .3), but SDD patients were younger (64 ± 11 vs. 66 ± 10; p < .0001) with lower body mass index (30 ± 6 vs. 31 ± 61; p < .0001) and CHA2 DS2 ‐VASc scores (1.4 ± 1.0 vs. 2.2 ± 1.4; p < .0002). There was no difference between SDD and ONS in the 30‐day total complication rate ( n = 15 [1.26%] versus n = 24 [2.03%]; p = .136, respectively). The most common complication was hematoma in both the SDD ( n = 8; 0.67%) and ONS ( n = 11; 0.93%) cohorts. Sensitivity analysis demonstrated that when 50% of every 100 patients treated were discharged the same day, hospital cost savings ranged from 45 825 to 83 813 per year across US hospitals. Conclusions: SDD following cryoballoon ablation for AF appears to be safe and is associated with cost savings across different US hospitals.